Improving the public service delivery thru E-government initiatives in Malaysia / Maniam Kaliannan and Jasmine Ahmad - Kaliannan, Maniam; Ahmad, Jasmine (2010)
This paper attempts to highlight how well Malaysia is progressing in improving the quality of civil service, via egovernment approach by making due references garnered from actual e-procurement experiences. The civil service itself is bogged down with host of challenges, some are new. In particular, growing expenditure arising from bloated civil service seems to have far reaching implications on much anticipated quality and productivity improvement. Nevertheless, the paper duly recognized the government’s commitments and its consistency in improving the quality and productivity of civil service all along since the nation gained its independence. In this endeavor, the contemporary ICT and e-government initiatives have been recognized as one of the way forward measures to up-lift the Malaysian civil service. Indeed, government adopted this measure not lately but two decades ago, when computerization and automation were regarded as a key to improve efficiency and effectiveness of all aspects and dimensions of civil service processes. Prior to proceeding to discuss the pertinent issues and challenges plaguing e-procurement services, the paper made a deliberate attempt to outline briefly the critical programme parameters that are imperative for spearheading the initiative. Despite these factors are put i place from onset of planning, the success of e-procurement initiative yet to be realized to its maximum potential, as per results of the case study. Indeed, this warrants due attention of policy makers and development practitioners, as well as industry players to rectify the weaknesses and gaps in moving forward.